Operation Dimwit : A Penelope Lemon Novel - Majors, Inman (Book collections on Project MUSE., 2020)
"Penelope Lemon, "a heroine for our age" (Los Angeles Review of Books), is back for more madcap mom adventures in Inman Majors's hilariously unruly "Operation Dimwit." It's summer time and son Theo is away at camp. Feeling frisky and free, and tired of living vicariously through nighttime erotic novels, Penelope can begin Phase 2 of her post-divorce life. First on the agenda is a date with the mysterious Fitzwilliam Darcy, who lives in a mansion with his snobbish cat, Algernon, and spends his spare time painting massive nude portraits. Nothing in her bedtime reading of Tycoon's Dare has prepared Penelope for an evening of this sort. Meanwhile, back at the trailer park office, her wild woman boss Missy has become obsessed with getting rid of Dimwit, the backwoods interloper who may be stealing personal items from women residents. A sting operation to catch him in the act is planned, something kooky and ill-advised that only a legendary goofball like Missy could set into motion. Throw in a bully trainer at Penelope's new gym, an infestation of skunks that requires the services of the wild life expert and homespun mystic known as the Critter Catcher, and further episodes with ex-husbands James and the HHR (huge, huge redneck), and it becomes clear that Penelope's two weeks off from parenting won't be as relaxing and incident free as she hoped. Continuing the comedic hijinks of "Penelope Lemon: Game On!," "Operation Dimwit" is a warm-hearted look at the challenges of being a single mom. Zany, stylish, and uproariously funny, this new installment of the Penelope Lemon saga will have readers laughing out loud at familiar absurdities of life in the twenty-first-century USA"--